Existence and uniqueness of continuous solution of mixed type integra equations in cone metric space - Tidke, HL; Aage, CT; Salunke, JN (Kathmandu University Journal of Science, Engineering and Technology, 2011)
In this paper we investigate the existence and uniqueness for Volterra-Fredholm type integral equations in cone metric spaces. The result is obtained by using the some extensions of Banach's contraction principle in complete cone metric space. Mathematics Subject Classification: 45N05, 47G20, 34K05, 47H10. Keywords: Cone metric space, Contractive mapping, ordered Banach space. DOI: http://dx.doi.org/ 10.3126/kuset.v7i1.5421 KUSET 2011; 7(1): 48-55